Commented translation of Heisenberg’s paper, “On the reinterpretation of kinematic and mechanical relations in quantum theory” (Cadernos de Astronomia, 2025)
We present the translation of the article published by Werner Heisenberg in 1925, which constitutes a landmark in the development of quantum mechanics. Some introductory comments are presented, followed by the Portuguese version of the text originally written in German.